(untitled) (The Research of Medical Science Review, 2024)
This study examines the health impacts of climate change in Karachi, Pakistan, highlighting the growing risks associated with rising temperatures, extreme weather events, and environmental degradation. It explores how these factors contribute to a range of health issues, including heat-related illnesses, respiratory problems, and the spread of vector-borne diseases. By analyzing health data and conducting interviews with healthcare professionals, the research reveals significant challenges faced by the city's healthcare system in addressing these climate-related health concerns. The findings underscore the need for proactive measures, including improved public health infrastructure and community awareness programs, to mitigate the adverse health effects of climate change in Karachi.